Spectral Quasilinearization Method for Solution of Convective Heating Condition - IBRAHIM, Wubshet (Engineering Transactions, 2020)
This article aims to implement the spectral quasilinearization method to examine the impact of a second-order slip flow and convective heating on boundary layer flow and heat transfer of a nanofluid over an extensible surface. The mathematical modeling of the flow problem is obtained by taking into consideration the weight of leading parameters. Similarity conversions are employed in converting the leading partial differential equations to non-linear high-order ordinary differential equations. These equations were numerically computed using a spectral quasilinearization method for different values of the main parameters. The interesting numerical outcomes are attained for the flow variables, as well as the skin friction coefficient, local Nusselt number and Sherwood number. The results designate that the skin friction coefficient $C_f$ falls as the values of slip parameter $γ$ rise, it improves as the values of $δ$ boost. Both the local Nusselt number, $θ'(0)$ , and Sherwood number, $φ'(0)$, drop as both Brownian motion and thermophoresis parameters increase. A comparison of the spectral quasilinerization method (SQLM) with the bvp4c method is conducted and an excellent agreement in their output is observed.